THE IMPACT OF MODERN PEDAGOGICAL CONDITIONS ON THE INFORMATION COMPETENCE FORMATION OF SOCIAL WORK GRADUATE STUDENTS - Kosteva, Tatiana; Faichuk, Elena (The Modern Higher Education Review, 2018)
The information competence of modern specialist, its structure and peculiarities of usage by future social worker are analyzed in the article. The author singles out four pedagogical conditions of information competence formation in social work undergraduates and determines their impact in everyday and professional life of future specialists. Expansion of application of informatively-communication technologies, socio-economic changes, process of integration of world community, stipulated the necessity of successive modernisation of the system of professional preparation of future specialists. Expansion of sharp problems of contemporaneity, that inherent to all spheres of public life, including actuality of paying attention to was stipulated social development workers. Authors are consider pedagogical technology of forming of informative competence of master's degrees of social work; innovative methodology of determination of profile of informative competence of master's degrees of social work is offered and entered in the modern measuring of organizational culture of university; essence of concept «informative competence of master's degrees of social work», basic contradictions of process of forming of informative competence, is specified; components, organizationally-pedagogical terms and principles of forming of informative competence of master's degrees of social work, are in an university;